Analisis Fundamental Terhadap Harga Saham Pada Bank Digital Periode 2021-2023 (Studi Kasus: PT Bank Jago Tbk) - Fadhillah, Ayu; Fadila, Ardhiani (Accounting Student Research Journal, 2025)
The purpose of this final project is to examine the fundamental factors affecting the stock price of PT Bank Jago Tbk during the period 2021–2023. The analytical methods used include fundamental company analysis using financial ratios: Debt to Equity Ratio (DER), Return on Equity (ROE), and Earnings Per Share (EPS). The results of this study indicate that the fundamental condition based on the financial ratio analysis of PT Bank Jago during the 2021-2023 period is as follows: the solvency analysis with the DER ratio is in the "Healthy" category, the profitability analysis with the ROE ratio is in the "Less Healthy" category, while the EPS ratio is in the "Good" category due to its increase.